GE_GERICHTE P/11883/2018 vom 27. Juli 2018 - GE Cour de justice (2018)
REQUÉRANT D'ASILE MINEUR NON ACCOMPAGNÉ ; OPPOSITION(PROCÉDURE) ; DÉFAUT(CONTUMACE) ; DÉFENSE D'OFFICE | PPMin.24; PPMin.25; CPP.355